Crime Watch: Hurricanes and Illegal Activities. (6th June 2019) - Spencer, Nekeisha; Strobl, Eric
Abstract : We investigate the relationship between hurricane strikes and crime for Jamaica. To this end, we construct hurricane damages and daily recorded criminal activity. Hurricanes are found to significantly increase crime by 35%, where the impact is stronger for more damaging storms, but this only lasts for the duration of the storm. Decomposing crime into its various subtypes, one finds that while aggravated assault, break‐ins, and shooting increase during a hurricane, murders, rapes, and robberies actually decline. The greatest increase is with shootings, whereas the greatest decline is with rape. Crucially, the impact of crime depends on the existence of a storm warning. Our results also show that high frequency data more accurately estimate the impact of hurricanes on crime.